A novel steel-PAFRC composite fender for bridge pier protection under low velocity vessel impacts. (August 2020) - Manohar, Titus; Suribabu, C.R.; Murali, G.; Salaimanimagudam, M.P.
Abstract: Steel fenders are frequently employed in bridge pier shields to engross collision energy due to vessel impact. However, vulnerability to corrosion is a major drawback in existing steel fenders. To end this, an innovative composite fender structure consisting of corrugated steel and Preplaced Aggregate Fibre Reinforced Concrete (PAFRC) is introduced. Corrugated plates of steel are intended to absorb energy and stiff guard outer panels made with PAFRC exhibit enhanced resistance to impact and ductility. Six steel-PAFRC fenders were prepared with the steel plates of two different thicknesses, where the four top panels of the PAFRC are reinforced with short and long hooked end steel fibres while bottom panels are made with non-fibrous preplaced aggregate concrete (PAC). All steel-PAFRC fenders were tested through a drop weight impact testing device to investigate their impact behaviour and failure mechanism. Collision energy at crack initiation and the ultimate crack of PAFRC panels, crushing deformation of corrugated plates and failure configuration were also examined. Additionally, a numerical model of composite fenders was developed and verified through experimental evidence. Research revealed the crashworthiness of PAFRC panel was higher when compared to the PAC panel. The relative resistance of corrugated plates of steel and the PAFRC panels had a dramatic effect on the composite fender's impact response.